Constitutional Foundations and Legal Restrictions on Mass Media Freedom in the Republic of Iraq - Naser Abdulridha, Jaafar; Jaber Hashim, Salwan; Batirovich Sultanov, Evgeny (International Journal of Criminology and Sociology, 2022)
This article is based on a research work done on Constitutional foundations and legal restrictions on freedom Mass media in the Republic of Iraq. Freedom of the media is a fundamental issue of democracy, because without freedom of the media there is no civil society or rule of law. Awareness of society is a necessary condition for its economic, political and cultural progress. The crucial role of the media and the danger of abuse of freedom of the press force democratic states to determine the legal status of the media and to regulate their activities. In the domestic scientific literature, the concepts of “freedom of information” and “freedom of mass media” are used in meanings that practically coincide with the meanings in which these concepts are used in the legislation of the Republic of Iraq. Only a general reference is made to the legislation of the Republic of Iraq on the media by which such restrictions are established. That is, the wording of Art. 73 reflect a clear imbalance between constitutionally substantiated rights and obligations of individuals related to the exercise of freedom of the media.